(untitled) (Journal of Engineering, 2012)
Rotating fan shaft system was investigated experimentally and theoretically to study its dynamic performance. The type of oil used for the bearing was taken in consideration during the experimental program .Three types of oil were used, SAE 40, SAE 50 and degraded oil. During the experiments, the fan blades stagger angle was changed through angles (20˚, 30˚, 40˚, and 50˚). The shaft rotational speed also changed in the range of (0-3000 rpm). All these parameters have investigated for two cases (balanced and unbalanced fan). The performance parameters of the fan were found experimentally by measuring the fan, volume flow rate, Reynolds and Strouhal numbers, efficiency and pressure head. Analytical part was also represented to prepare the prediction of fan system dynamic performance. The aerodynamic forces and moments of each blade were also predicted to obtain the rotor dynamic future. Experimentally and theoretically the critical fan speed was obtained in the x and y direction for different lubricant oil viscosities and shaft rotational velocities for balanced and unbalanced fan. Analysis of the vibrational response gave important information about the dynamic performance of fan rotating system. Acceptable agreement was found between analytical and experimental results.